Economic and legal essence of compliance - security of international business - Tkachоv, M. M.; Kosenko, S. A. (Харківський національний університет міського господарства імені О. М. Бекетова, 2025)
The scientific report proves that compliance security is an integral element of modern international business, which helps to reduce legal risks, strengthen trust on the part of partners and consumers, as well as increase the competitiveness of the company. ensures its long-term security and sustainability on the world stage.
Економіко-правова сутність комплаєнс - безпеки міжнародного бізнесу
Keywords: international business; compliance; economic security; industrial enterprises; legal protection; efficiency